Kontribusi Pondok Pesantren Haji Ya’qub Lirboyo Kediri dalam Mengembangkan Pendidikan Politik Islam di Indonesia - Ahmad Sodikin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
Speaking of pesantren and Islamic politics, it cannot be separated from Islam and its people, while Muslims have been encouraged by their leaders (although in minority number) that to not mix religion with politic, especially in Indonesia in the 1980s so that there is an impression that Muslims do not need to engage in politic mainly in the pesantren community and that's why Muslims and their leaders become afraid talking about politics. It encourages the writer to find out more about how political education in pesantren which finally the writer do research in the pesantren in particular pesantren of Haji Ya'qub Lirboyo in Kediri. The type of research used was qualitative descriptive. Because the research aimed to describe the phenomena at the research location. This research succeeded in obtaining findings according to the problem questions which in the outline can be summarized as follows: Islamic political education in pesantren of Haji Ya'qub Lirboyo indirectly existed since the time of its establishment, but limited only to the role model of the kyais. On the other hand, the form of political education such as organizations still exist, for example Jamiyyah, Bahtsul Masa'il Institution, and Madrasah Diniyah. While education that is purely in the form of lesson is understanding Nahdlatul Ulama (NU) and Civics that learned in public school. Contribution of Haji Ya'qub Islamic boarding school in Islamic political education consisted of two types which is fund and behavior. In the form of fund contribution was donation to the local election committee. Whereas in the form of the behavior, the Haji Ya'qub Islamic boarding school formed organizations such as LBM, Jamiyyah, and Madrasah Diniyah.